2015
DOI: 10.1177/0951629815586873
|View full text |Cite
|
Sign up to set email alerts
|

Increasing rents and incumbency disadvantage

Abstract: Recent empirical studies have found a incumbency disadvantage in many developing democracies, in marked contrast with the well-known incumbency advantage in the US and other developed democracies. We know considerably less about incumbency disadvantage than incumbency advantage. In a simple principal-agent framework, I explore the role of a prominent feature of developing democracies -corruption. When rents are constant in incumbents' tenure -a standard assumption -the conditions for incumbency disadvantage ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 90 publications
1
16
0
3
Order By: Relevance
“…The International Social Survey Programme (ISSP) contains satisfactory corruption items in addition to political variables, but these are only present in a single cross-section conducted as part of the 2006 Role of Government IV module. 37 See for example Birch (2003); Klasˇnja (2013a); Pop-Eleches (2010); Roberts (2008). In one of the few direct tests of the relationship between corruption and voting in a post-communist country, Slomczynski and Shabad (2011) show that perceiving a party to be corrupt made voters in Poland less likely to vote for that party.…”
Section: Focus and Datamentioning
confidence: 98%
“…The International Social Survey Programme (ISSP) contains satisfactory corruption items in addition to political variables, but these are only present in a single cross-section conducted as part of the 2006 Role of Government IV module. 37 See for example Birch (2003); Klasˇnja (2013a); Pop-Eleches (2010); Roberts (2008). In one of the few direct tests of the relationship between corruption and voting in a post-communist country, Slomczynski and Shabad (2011) show that perceiving a party to be corrupt made voters in Poland less likely to vote for that party.…”
Section: Focus and Datamentioning
confidence: 98%
“…De acuerdo con Klasnja (2011), hay al menos dos razones distintas acerca de por qué la búsqueda de rentas puede ser más alta en una democracia joven que en una desarrollada. En primer lugar, hubo poco tiempo para que los políticos, así como los partidos políticos, puedan establecer reputaciones.…”
Section: Discusión Sobre Los Resultados: Posibles Causasunclassified
“…Siguiendo la literatura teórica reciente, el trabajo de Klasnja (2011), propone la hipótesis de que en un contexto político-institucional débil con relativamente altos niveles de corrupción, como el de Guatemala y otros países en desarrollo, la capacidad de extracción de rentas de los incumbentes es creciente en el tiempo. Luego el efecto incumbente negativo surgiría como un intento de los votantes por limitar la búsqueda de rentas por parte de los políticos en el poder.…”
Section: Introduccionunclassified
“…Scholars have nevertheless shown that an incumbency advantage can emerge due to noisy signaling by incumbents using messages that are payoff irrelevant to voters (Caselli, Cunningham, Morelli and Moreno de Barreda, 2014), voters imperfectly observing previous electoral margins (Fowler, 2018), or learning by doing (Dick and Lott, 1993) and legislative seniority rules (Muthoo and Shepsle, 2014;Eguia and Shepsle, 2015). Incumbency disadvantage can emerge when a politician's ability to secure personal rents increases with tenure (Klašnja, 2016). Eggers (2017) demonstrates that either incumbency advantage or disadvantage can be generated by non-random retirements as well as by asymmetries or trends in the distribution of politicians' quality.…”
mentioning
confidence: 99%
“…The crux of our theory is a decline in the effects of accountability over a politician's tenure in office; this decline may owe to either the politician's political horizon (under term limits, as in Sections 1-2) or from the electorate's information (when type is revealed in office, as in Section 3). One can view our theory as combining this decline with the nature of reputation effects to offer a unified microfoundation for why politicians may become more effective (Dick and Lott, 1993;Muthoo and Shepsle, 2014;Eguia and Shepsle, 2015) or more corrupt (Klašnja, 2016) over their career; the former emerges under bad reputation effects while the latter emerges under good reputation effects.…”
mentioning
confidence: 99%